Pemilihan Media Digital Dalam Pemasaran Produk Keripik Di Bekasi - Nunu Kustian Nunu Kustian; Syamsiah; Siti Julaeha (Elkom : Jurnal Elektronika dan Komputer, 2023)
Digital marketing is an important part of promoting a business owned by an individual or an organization. Marketing is essential for startups to stay competitive and sustain their products on the market. For people who are computer novices, this is a challenge. One of them is the proprietor of Keripik Orang Kekinian, a chips company in Bekasi, Indonesia, which has limited sales capabilities for its product. Researchers help firms choose the best social media channels for promoting their products in order to overcome these difficulties. The methods involved are Simple Additive Weighting (SAW) and Analytical Hierarchy Processing (AHP). The results show that Instagram is the best social media platform for advertising products. The result obtained are expected to help business owners increase sales.